How do people with physical/mobility disabilities benefit from a telehealth exercise program? A qualitative analysis - Wilroy, Jereme D.; Kim, Yumi; Lai, Byron; Ivankova, Nataliya; Herbey, Ivan; Sinha, Tanvee; Rimmer, James H. (Frontiers in Rehabilitation Sciences, 2022)
People with neurological and physical disabilities (PWD) experience a myriad of secondary and chronic health conditions reducing participation and quality of life. A telehealth exercise program could provide a convenient opportunity for improving health in this population. To describe participants’ perceived benefits of a telehealth physical activity program among PWD, we conducted semi-structured interviews with 30 study participants after completing the 24-week program SUPER-HEALTH (Scale Up Project Evaluating Responsiveness to Home Exercise And Lifestyle TeleHealth). Interview data were recorded, transcribed verbatim, and analyzed using inductive thematic analysis. The mean age of the sample was 51 ± 13 years, primary disability was Multiple Sclerosis, and there were 9 males (30.0%) and 21 (70.0%) females. Inductive thematic analysis resulted in 4 themes including 1) improved health and function, 2) increased activity participation, 3) improved psychosocial health, and 4) optimized performance and benefits. These preliminary findings provide support for the use of a home exercise program and recommendations to improve it to enhance benefits among PWD.